Pengaruh Media Pembelajaran dalam Discovery Learning dan Penguasaan Pilihan Kata Terhadap Kemampuan Menulis Cerita Pendek - Rahmadani, Diah (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This study aims to determine the effect of instructional media (audio-visual and print) in discovery learning and mastery of word choice and whether there is an interaction effect between the two on the ability to write short stories. Instructional media used in this study is the instructional media audio-visual and learning media print in discovery learning. While the choice of words distinguished mastery over control over the choice of words high and low mastery of word choice. The method used is an experimental method using a 2x2 factorial design. Measurement variable short story writing skills is using written tests and mastery of word choice to use multiple-choice test. Data analysis techniques in this study is the technique of analysis of variance (ANOVA) followed by two lanes and Tuckey test to see the group interaction. Prior to testing hypotheses, test requirements analysis is the normality test data using test Liliefors and homogeneity of variance test using test equality of two variances.   The results of this study can be summarized as follows: There is a learning media influence on the ability to write short stories. This can be seen from the sig. 007 There is a media interaction effect of learning and mastery of word choice in the ability to write short stories. This can be seen from the sig. Fhitung 0.000 and 51.290. There is a mastery of word choice influence on the ability to write short stories with the audio-visual media group media group prints at high word selection capability. This can be seen from the sig value 0,000 smaller than the error level of 0.05. There is a mastery of word choice influence on the ability to write short stories with the audio-visual media group media group prints on the ability of wording low. This can be seen from the sig value 0,008 lower than the level of 0.05 The results of this study are expected to be useful for the improvement of the learning process in the classroom to improve teaching skills; the teacher becomes a facilitator in the learning activities.